The Role of Islamic College Library in Supporting the Implementation of Sustainable Development Goals 4 Program - Lestari, Putri; Purwaningtyas, Franindya (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to identify the role of the library of Al-Ulum Integrated Islamic Colllege in supporting the Implementation of Sustainable Development Goals 4. The research method used is qualitative method using semi-structured interviews as a data collection technique. The data sources used in this study were stakeholders, students, librarians, and libraries at Al-Ulum Medan Integrated Islamic College. The collected data is then analyzed using thematic analysis. The results of the analysis show two themes, namely programs, and constraints. The program theme explains the role that libraries play in supporting the implementation of SDGs 4. This theme tells about providing access to information to users, library cooperation programs with other parties who also contribute to supporting the implementation of SDGs 4, as well as training programs to develop human resources. The constraint theme illustrates the activities or policies in the library that can hinder the library from providing support in the implementation of SDGs 4. This research contributes to providing new knowledge on how libraries play a role in supporting the implementation of Sustainable Development Goal 4